Ammonia removal from digested swine wastewater using a High-Performance Rotating Reactor - Trinh, Viet M.; Van Tuyen Trinh,; Nguyen, Phuong Thao; Pham, Huu Tung; Nguyen, Tuan Minh; Do, Van Manh; Ngo, Thanh Long (Vietnam Journal of Science and Technology, 2024)
The wastewater generated from the livestock industry is an enormous source of pollution that is challenging the sustainable development of the agricultural sector. Even the anaerobic digestion is adopted, the characteristic of the digested wastewater is still way polluted compared to the discharge standard. The high content of ammonia in this wastewater resulted in a low C/N ratio, consequently inhibiting the aerobic biological treatment. Hence, it is necessary to pretreat the excessive concentration of ammonia from the input stream of livestock wastewater. The High-Performance Rotating Reactor (HP2R) equipment has been proven to be a promising and advanced equipment to remove high concentrations of ammonia from synthetic wastewater via stripping. Therefore, ammonia removal using HP2R equipment was comprehensively studied with the digested swine wastewater under various operational conditions. In this study, the effects of pre-alkalinization (pHi), rotating speed (ω), gas flow rate (QG), and swine wastewater flow rate (QL) on the ammonia removal efficiency (ARE) and the overall liquid mass transfer coefficient (KLa) was evaluated. The results indicated that the HP2R could effectively remove ammonia from the wastewater in instant batch mode at a laboratory scale. The ARE by stripping via HP2R varied from 33% to 78% at various gas and liquid flow rate with the pre-alkalinization of swine wastewater pHi of 11, ω of 900-1200 rpm, and the initial ammonia concentration of approximately 660 mg/L. Especially, the mass transfer of the process was enhanced compared to the conventional packed column as the KLa varied from 0.0014 s-1 to 0.0038 s-1.